A Bacterial Inflammation Sensor Regulates c-di-GMP Signaling, Adhesion, and Biofilm Formation - Arden Perkins (American Society for Microbiology, 2021)
Immune cells are well equipped to eliminate invading bacteria, and one of their primary tools is the synthesis of bleach, hypochlorous acid (HOCl), the same chemical used as a household disinfectant. In this work, we present findings showing that many host-associated bacteria possess a bleach-sensing protein that allows them to adapt to the presence of this chemical in their environment.